The Social and Political Study of Philip Larkin’S Selected Poems: Exploring the Life and Works of Philip Larkin (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Philip Arthur Larkin (9 August 1922 – 2 December 1985) iswidely regarded as one of the greatest English poets of the latter half of thetwentieth century. His first book of poetry, The North Ship, was published in1945, followed by two novels, Jill (1946) and A Girl in Winter (1947), but hecame to prominence in 1955 with the publication of his second collection ofpoems, The Less Deceived, followed by The Whitsun Weddings (1964) and HighWindows (1974). He contributed to The Daily Telegraph as its jazz critic from1961 to 1971, articles gathered together in All What Jazz: A Record Diary1961–71 (1985), and he edited the Oxford Book of Twentieth-Century EnglishVerse (1973). He was offered, but declined, the position of poet laureate in1984, following the death of John Betjeman.